2006
DOI: 10.1002/jbm.a.30977
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption on polyurethane catheters modified with a novel antithrombin‐heparin covalent complex

Abstract: Highly anticoagulant covalent antithrombin-heparin complex (ATH) was covalently grafted onto polyurethane catheters to suppress adsorption/activation of procoagulant proteins and enhance adsorption/activation of anticoagulant proteins for blood compatibility. Consistency of catheter coating was demonstrated using immunohistochemical visualization of ATH. The ability of the resulting immobilized ATH heparin chains to bind antithrombin (AT) from plasma, as measured by binding of 125 I-radiolabeled AT, was greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 89 publications
1
42
0
Order By: Relevance
“…Polyurethanes, in particular, are attractive supports due to their rapid and simple preparation and tunable properties that, when used as scaffolds, yield stable bioplastics (Drevon et al, 2001(Drevon et al, , 2002Gill and Ballesteros, 2000;Gordon et al, 1999;LeJeune et al, 1997LeJeune et al, , 1999Vasudevan et al, 2004). Additionally, as polymers and coatings for implantable materials and medical devices, including catheters and metal stents, polyurethanes are widely used in tissue engineering and regenerative medicine (Du et al, 2007;Guelcher, 2008;Klement et al, 2006;Santerre et al, 2005;Trigwell et al, 2006). Bakker et al (2000) have previously shown that acylase could be immobilized in polyurethane foams while retaining activity, although such foams are impractical for use as coatings on catheter surfaces.…”
Section: Preparation and Activity Of Acylase-containing Coatingsmentioning
confidence: 99%
“…Polyurethanes, in particular, are attractive supports due to their rapid and simple preparation and tunable properties that, when used as scaffolds, yield stable bioplastics (Drevon et al, 2001(Drevon et al, , 2002Gill and Ballesteros, 2000;Gordon et al, 1999;LeJeune et al, 1997LeJeune et al, , 1999Vasudevan et al, 2004). Additionally, as polymers and coatings for implantable materials and medical devices, including catheters and metal stents, polyurethanes are widely used in tissue engineering and regenerative medicine (Du et al, 2007;Guelcher, 2008;Klement et al, 2006;Santerre et al, 2005;Trigwell et al, 2006). Bakker et al (2000) have previously shown that acylase could be immobilized in polyurethane foams while retaining activity, although such foams are impractical for use as coatings on catheter surfaces.…”
Section: Preparation and Activity Of Acylase-containing Coatingsmentioning
confidence: 99%
“…The open ends of the PCI catheters were sealed with implant-grade silicone adhesive (Rhodia, Ventura, CA). Using the procedure of Du et al [29], a base coat was first applied by immersing the catheter segments in a 10 ml solution of glycidyl methacrylate containing 0.1 g AIBN for 20 min at 23°C. After removing the catheters, excess solution was blotted with filter paper and the catheters were incubated at 80°C for 40 min followed by an annealing step at 50°C for 20 min.…”
Section: Catheter Modificationmentioning
confidence: 99%
“…The anticoagulant activity of the heparinized surfaces depends on the ability of immobilized heparin to bind to AT. It is reported that heparinized surfaces can have variable anticoagulant activity, and negatively charged long heparin chains may also promote protein binding and platelet aggregation [8,9].…”
Section: Introductionmentioning
confidence: 99%